The Role of Indirect Laryngoscopy, Clinical and Ultrasonographic Assessment in Prediction of Difficult Airway. (30th July 2020) - Altun, Demet; Kara, Hakan; Bozbora, Erol; Ali, Achmet; Dinç, Tuğçe; Sonmez, Said; Buget, Mehmet; Aydemir, Levent; Basaran, Bora; Tuğrul, Mehmet; Çamci, Emre
Abstract : Objectives: Pre‐operative airway evaluation is essential to decrease the proportion of possible mortality and morbidity due to difficult airway (DA). The study aimed to evaluate the accuracy of pre‐operative ultrasonographic airway assessment (UAA) and indirect laryngoscopy (IL) in predicting DA. Study Design: Prospective obsevational study. Methods: Preoperative clinical examination (body mass index [BMI], mallampati classification [MP], thyromental distance, sternomental distance, neck circumference), UAA (epiglottis‐skin distance [ESD], hyoid bone‐skin distance [HSD], the thickness of tongue root [ToTR], anterior commissure‐skin distance [ACSD]) and IL with the rigid 70‐degree laryngoscope were performed to predict DA (Cormack‐Lehane grade 3 and 4). The sensitivity, specificity, positive predictive value (PP), and negative predictive values of the parameters were assessed. Results: Twenty‐two of 140 (15.7%) patients were diagnosed with DA. The cut‐off points of ESD, HSD, ToTR, ACSD, and BMI were 2.09 cm, 0.835 cm, 4.05 cm, 0.545 cm, and 27.10, respectively. AUC values were 0.874, 0.885, 0.871, 0.658, and 0.751 in the same order. AUC values for IL and MP were 0.773 and 0.925, respectively. MP and HSD had the best sensitivity (91%), IL grading had the best specificity (100%), and PP (100%) value among all measurements. The best‐balanced sensitivity (91%), specificity (97%), and PP (88%) values were obtained by combining the IL with MP and ESD or with MP and HSD. Conclusions: Ultrasonographic measurements and IL were found significantly correlated to predict DA. Combined parameters, the IL with MP and ESD or with MP and HSD, are the best parameters in predicting the DA. Level of Evidence: 4 Laryngoscope, 131:E555–E560, 2021